Enter only a number for your answer.
Answer:
-4
Step-by-step explanation:
Notice that the only way to multiply 2 numbers from each of the polynomials and get an x term is to multiply a constant and an x term.
The only ways to do that is to multiply -6x by 3 and 7x by 2.
After you're done multiplying, just combine the 2 like terms:
-18x+14x
=-4x
Therefore, the coefficient of the x term is -4.
3 pts
Select the three equations that are also equivalent to 0.5 +10b+4= 19.5
A. 106 +4= 19.5
B. 10b +4=19
C. 2(0.5 +10b+ 4) = 39
D. 10b= 19.5
E. 10b= 15
Answer:
Equation (B) and (C) are equal to 0.5+10b+4=19.5
As in equation (B) when we take the 0.5 on the other side, the sign will change.Then the equation will be 10b+4=19.5-0.5
Which equals : 10b+4=19
In equation (C) 2(0.5+10b+4)=39
The 2 which is being multiplied to the bracket equation will be canceled out when we divide it , and will be divided on the other side as well so 39÷2=19.5
So the equation will become 0.5+10b+4=19.5
B With = 12 and length = 29
C With = 14 and length = 31
D With = 16 and length = 32